2015
DOI: 10.1002/ente.201500154
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Bulk‐Heterojunction Solar Cells using Polyethylenimine‐Ethoxylated Processed from a Fully Aqueous Dispersion as Electron‐Transport Layer

Abstract: In this work, we present the realization and characterization of bulk‐heterojunction (BHJ) solar cells in which we use a spin‐coated polyethylenimine‐ethoxylated (PEIE) layer as electron‐transporting layer deposited from a fully water‐based solution. We investigated several concentrations of PEIE in aqueous solution and characterized the chemical and electrical behavior of PEIE‐coated fluorinated tin oxide (FTO) substrates. We realized BHJ solar cells using P3HT:PC60BM as active layer achieving a maximum effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As reported in Figure b, the ITO electrode shows quasi‐metallic behavior when highly doped. ITO represents a Schottky‐type contact at both ITO/polymer and ITO/fullerene interfaces, and band bending can be disregarded due to a high carrier density and to the typically large amount of ITO surface trap states . In the case of metal–organic interfaces, a Pauli “push‐back” effect occurs and a charge transfer into the metal is observed, thus determining the final contact energy level …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in Figure b, the ITO electrode shows quasi‐metallic behavior when highly doped. ITO represents a Schottky‐type contact at both ITO/polymer and ITO/fullerene interfaces, and band bending can be disregarded due to a high carrier density and to the typically large amount of ITO surface trap states . In the case of metal–organic interfaces, a Pauli “push‐back” effect occurs and a charge transfer into the metal is observed, thus determining the final contact energy level …”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, we demonstrated the preparation of a spray‐coated active layer using low‐bandgap polymers such as poly[[4,8‐bis[(2‐ethylhexyl)oxy]benzo[1,2‐b:4,5‐b’]dithiophene‐2,6‐diyl][3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3,4‐b]thiophenediyl]] (PTB7) and 2,6‐bis(trimethyltin)‐4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1,2‐b:4,5‐b’]dithiophene (PBDTTT‐C‐T) along with xylene, which is a nonchlorinated solvent with low amounts of volatile organic compounds compared to chlorinated solvents. It has been demonstrated that a polyethylenimine ethoxylated (PEIE)‐based electron transporting layer (ETL) can be prepared by replacing the more toxic 2‐methoxyethanol with eco‐friendly solvents, such as water or ethanol, to allow the use of another electron selective layer such as zinc oxide (ZnO) . There has been no progress in the production of a full spray polymeric device; indeed, in the work of Zhang et al, only two layers (PAL and hole transporting layer [HTL]) are reported in the direct structure.…”
Section: Introductionmentioning
confidence: 99%
“…Organic photovoltaic devices are able to deliver photocurrents thanks to the generation of electrical fields when light is absorbed in their photoactive layers, composed of a donor, and an acceptor semiconducting material. The donor material donates electrons transporting holes while the acceptor material withdraws electrons and further transports them (Polino et al, 2015 ).…”
Section: Electrical Phototransduction In Devices For Biomedical Applimentioning
confidence: 99%